Implicit learning in individuals with autism spectrum disorders: a meta-analysis. Issue 5 (15th August 2014) - Foti, F.; De Crescenzo, F.; Vivanti, G.; Menghini, D.; Vicari, S.
Abstract : Background: Individuals with autism spectrum disorders (ASDs) are characterized by social communication difficulties and behavioural rigidity. Difficulties in learning from others are one of the most devastating features of this group of conditions. Nevertheless, the nature of learning difficulties in ASDs is still unclear. Given the relevance of implicit learning for social and communicative functioning, a link has been hypothesized between ASDs and implicit learning deficit. However, studies that have employed formal testing of implicit learning in ASDs provided mixed results. Method: We undertook a systematic search of studies that examined implicit learning in ASDs using serial reaction time (SRT), alternating serial reaction time (ASRT), pursuit rotor (PR), and contextual cueing (CC) tasks, and synthesized the data using meta-analysis. A total of 11 studies were identified, representing data from 407 individuals with ASDs and typically developing comparison participants. Results: The results indicate that individuals with ASDs do not differ in any task considered [SRT and ASRT task: standardized mean difference (SMD) −0.18, 95% confidence interval (CI) −0.71 to 0.36; PR task: SMD −0.34, 95% CI −1.04 to 0.36; CC task: SMD 0.27, 95% CI −0.07 to 0.60]. Conclusions: Based on our synthesis of the existing literature, we conclude that individuals with ASDs can learn implicitly, supporting the hypothesis that implicit learning deficits do not represent a core feature in ASDs.